Rate coefficients for the reactions of OH with butanols from 298 K to temperatures relevant for low‐temperature combustion. Issue 12 (7th September 2020) - Sime, Samantha L.; Blitz, Mark A.; Seakins, Paul W.
Abstract: Rate coefficients for the reactions of OH with n, s, and iso‐butanol have been measured over the temperature range 298 to ∼650 K. The rate coefficients display significant curvature over this temperature range and bridge the gap between previous low‐temperature measurements with a negative temperature dependence and higher temperature shock tube measurements that have a positive temperature dependence. In combination with literature data, the following parameterizations are recommended: k 1, OH + n‐butanol ( T ) = (3.8 ± 10.4) × 10 −19 T 2.48 ± 0.37 exp ((840 ± 161)/ T ) cm 3 molecule −1 s −1 k 2, OH + s‐butanol ( T ) = (3.5 ± 3.0) × 10 −20 T 2.76 ± 0.12 exp ((1085 ± 55)/ T ) cm 3 molecule −1 s −1 k 3, OH + i‐butanol ( T ) = (5.1 ± 5.3) × 10 −20 T 2.72 ± 0.14 exp ((1059 ± 66)/ T ) cm 3 molecule −1 s −1 k 4, OH + t‐butanol ( T ) = (8.8 ± 10.4) × 10 −22 T 3.24 ± 0.15 exp ((711 ± 83)/ T ) cm 3 molecule −1 s −1 Comparison of the current data with the higher shock tube measurements suggests that at temperatures of ∼1000 K, the OH yields, primarily from decomposition of β‐hydroxyperoxy radicals, are ∼0.3 ( n ‐butanol), ∼0.3 ( s ‐butanol) and ∼0.2 (iso‐butanol) with β‐hydroxyperoxy decompositions generating OH, and a butene as the main products. The data suggest that decomposition of β‐hydroxyperoxy radicals predominantly occurs via OH elimination.